2000
DOI: 10.1211/146080800128735953
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB<SUB>1</SUB> Receptors Are Involved in the Regulation of Rat Gastric Acid Secretion

Abstract: The effects of cannabinoid CB1 receptor activation (HU‐210) and blockade (SR141716A) on gastric acid secretion were determined in anaesthetized rats with lumen perfused stomach. The selective CB1‐receptor agonist HU‐210 (0.01‐0‐1 mg kg−1, i.v.) did not affect basal acid secretion while causing inhibition (maximum reduction 74%) of the gastric acid secretion stimulated by pentagastrin (10μ kg−1, i.v.). The inhibitory effect of HU‐210 was reversed by the selective cannabinoid CB1‐receptor antagonist SR141716A (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The present study showed that CB 1 receptors mediate the inhibitory eects of CB-receptor agonists on the acid secretion induced by pentagastrin and 2-deoxy-D-glucose in the anaesthetized rat. These data con®rm and extend previous studies indicating that CB-receptor agonists reduced the secretory eects of single administrations of pentagastrin (Coruzzi et al, 1999;Adami et al, 2000). The two agonists employed in this study, namely WIN 55,212-2 and HU-210, behaved similarly in reducing pentagastrin and 2-deoxy-Dglucose, being HU-210 approximately 10 times more potent than WIN 55,212-2.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study showed that CB 1 receptors mediate the inhibitory eects of CB-receptor agonists on the acid secretion induced by pentagastrin and 2-deoxy-D-glucose in the anaesthetized rat. These data con®rm and extend previous studies indicating that CB-receptor agonists reduced the secretory eects of single administrations of pentagastrin (Coruzzi et al, 1999;Adami et al, 2000). The two agonists employed in this study, namely WIN 55,212-2 and HU-210, behaved similarly in reducing pentagastrin and 2-deoxy-Dglucose, being HU-210 approximately 10 times more potent than WIN 55,212-2.…”
Section: Discussionsupporting
confidence: 90%
“…We have previously reported that two synthetic CBreceptor agonists, the aminoalkylindole WIN 55,212-2 and the tricyclic cannabinol derivative HU-210, signi®cantly reduced pentagastrin-induced acid secretion in the anaesthetized rat, whereas the selective CB 2 -receptor agonist JWH-015 had no eect (Coruzzi et al, 1999;Adami et al, 2000). In the present study, the mechanism underlying the gastric antisecretory eects of the mixed CB 1 /CB 2 -receptor agonist WIN 55,212-2 and of the selective CB 1 -receptor agonist HU-210 was investigated in the anaesthetized rat on the production of acid induced by direct stimuli of the oxyntic cells (histamine), or by indirect stimuli (2-deoxy-D-glucose and pentagastrin).…”
Section: Introductionmentioning
confidence: 99%
“…Histological examination confirmed the weak damage presented in the stomach of rats treated with WIN 55,212-2 and its reversal by SR141716A. The antiulcer effect of WIN 55,212-2 could be related to its antisecretory effects as it has been recently shown that it reduces acid secretion stimulated by pentagastrin in the rat in vivo via activation of CB 1 receptors (Coruzzi et al 1999;Adami et al 2000). It is worthy to note that activation of cannabinoid CB 1 receptors causes reduction of gastric motility (Izzo et al 1999b) and intestinal secretion (Izzo et al 1999a) in the rat in vivo.…”
Section: Discussionmentioning
confidence: 56%
“…With regard to the gastric functions, it has been recently shown that the cannabinoid receptor agonists reduce gastric motility (Izzo et al 1999a;Krowichi et al 1999) and gastric acid secretion (Coruzzi et al 1999;Adami et al 2000) in rat in vivo via activation of cannabinoid CB 1 receptors; furthermore, a preliminary report showed immunohistochemical localization of cannabinoid CB 1 receptors on acetylcholine-containing neurones that innervate smooth muscle, mucosa and submucosal blood vessels of the rat stomach Izzo et al 2000). In the present work we have evaluated the possible antiulcer effect of the cannabinoid agonist WIN 55,212-2 and studied its effect in the presence of the cannabinoid CB 1 receptor antagonist SR141716A (Rinaldi-Carmona et al 1995) or the cannabinoid CB 2 receptor antagonist SR144528 (Rinaldi-Carmona et al 1998).…”
Section: Introductionmentioning
confidence: 99%